2008
DOI: 10.1111/j.1471-0528.2008.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit for maternal and newborn health services in resource‐poor countries

Abstract: Please cite this paper as: Kongnyuy E, van den Broek N. Audit for maternal and newborn health services in resource-poor countries. BJOG 2009;116:7-10. Each year more than 536 000 women worldwide die from complications of pregnancy and childbirth. 1 Many more survive but will suffer ill health and disability as a result of these complications. In addition, an estimated 4 million neonatal deaths occur each year, accounting for almost 40% of all deaths in children younger than 5 years. 2 The key strategies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…van den Akker et al, (2011) and Dumont et al , (2006) respectively showed that in a period of two to three years systemic audit and feedback in busy district hospitals helped to improve management of haemorrhage and ruptured uterus and reduced CFR due to these two conditions by 45–68% respectively [34], [35]. It is recommended that all cadres of providers who are involved in maternal care as well as members of the community should be part of the maternal audit team [34]–[36]. This will ensure feedback is shared and action is taken to improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…van den Akker et al, (2011) and Dumont et al , (2006) respectively showed that in a period of two to three years systemic audit and feedback in busy district hospitals helped to improve management of haemorrhage and ruptured uterus and reduced CFR due to these two conditions by 45–68% respectively [34], [35]. It is recommended that all cadres of providers who are involved in maternal care as well as members of the community should be part of the maternal audit team [34]–[36]. This will ensure feedback is shared and action is taken to improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…All three essentially ask the following questions: What was done well, what was not done well and how can care be improved in future? [60].…”
Section: Adaptations Of the General Cmnh-lstm Emonc Packagementioning
confidence: 95%
“…31 Where the need relates, for example, to preventing maternal and newborn deaths, the audit and feedback process of gathering, reviewing and acting-upon information on these adverse events is one of the keystones to Continuous Quality Improvement strategies in MNH care. 32 A Cochrane review of randomised controlled trials of audit and feedback showed a greater impact on health care practices and outcomes than other improvement strategies. 30 Whilst there is an ever-expanding number of tools and approaches for improving and assuring different elements of quality, two of particular relevance to MNH are death audit and standards or criterion-based audit.…”
Section: Tools and Approaches For Quality Improvementmentioning
confidence: 99%